Uporaba antikonvulzivnih zdravil pri zdravljenju afektivnih motenj - Žmitek, Andrej (Medicinski razgledi, 1998)
An ideal medical treatment for affective disorders is not yet available. Specific needs of individual patients can be met by selecting from among a wide range of drugs on the market. The authors review literature on the use ofanticonvulsants in patients with affective disorders. They discuss various aspects of this therapy: treatment and prophylaxis of manic and depressive episodes; side effects, drug interactions and mechanisms of action of anticonvulsants. Some basic instructions about therapy are given. The authors feel that anticonvulsants are a good alternative to other drugs used to treat affective disorders.
Keywords: Affective disorders; duševne motnje; motnje razpoloženja; Drug therapy; Anticonvulsants; therapy; zdravljenje; zdravila; Administration and dosage; drug; Adverse effects; Pharmacology; Carbamazepine; Valproic acid